PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN KURIKULUM MERDEKA BELAJAR - Miftahul Huda (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the role of the principal in the development and implementation of the Merdeka Belajar Curriculum. Using a qualitative approach with a case study at SMP NU Islami Pesanggaran Banyuwangi, data were collected through in-depth interviews, participant observation, and document analysis. Principals play an important role in the development and implementation of an effective Merdeka Belajar Curriculum in schools. Their leadership determines the success of curriculum innovation, through resource management, teacher motivation, and the creation of a conducive learning environment. The results of the study show that active and innovative principals have succeeded in improving the quality of learning and student engagement. In addition, teacher motivation and creativity in designing project-based learning have also increased. the role of the principal is very vital in the development and implementation of the Merdeka Belajar Curriculum. An effective principal not only manages resources well, but also motivates and empowers teachers and creates an innovative and collaborative learning environment. The success of implementing the Merdeka Belajar Curriculum is highly dependent on the quality of the principal's leadership, who is proactive in supporting teachers and providing a clear vision